2008
DOI: 10.1111/j.1742-4658.2008.06395.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of D‐arabinose in mycobacteria – a novel bacterial pathway with implications for antimycobacterial therapy

Abstract: Decaprenyl-phospho-arabinose (b-d-arabinofuranosyl-1-O-monophosphodecaprenol), the only known donor of d-arabinose in bacteria, and its precursor, decaprenyl-phospho-ribose (b-d-ribofuranosyl-1-O-monophosphodecaprenol), were first described in 1992. En route to d-arabinofuranose, the decaprenyl-phospho-ribose 2¢-epimerase converts decaprenyl-phospho-ribose to decaprenyl-phospho-arabinose, which is a substrate for arabinosyltransferases in the synthesis of the cell-wall arabinogalactan and lipoarabinomannan pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
162
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(169 citation statements)
references
References 140 publications
(216 reference statements)
4
162
0
1
Order By: Relevance
“…Mtb Decaprenylphosphoryl‐β‐ d ‐ribofuranose 2‐oxidase (DprE1) is a flavin adenine dinucleotide (FAD)‐dependent enzyme, which together with decaprenylphosphoryl‐ d ‐2‐ketoerythropentose reductase (DprE2), converts decaprenylphosphoryl‐beta‐ d ‐ribose (DPR) to decaprenylphosphoryl‐beta‐ d ‐arabinofuranose (DPA), an essential cell wall component 1. Conditional knockdown studies showed that loss of dprE1 results in a strong bactericidal effect in vitro 2.…”
mentioning
confidence: 99%
“…Mtb Decaprenylphosphoryl‐β‐ d ‐ribofuranose 2‐oxidase (DprE1) is a flavin adenine dinucleotide (FAD)‐dependent enzyme, which together with decaprenylphosphoryl‐ d ‐2‐ketoerythropentose reductase (DprE2), converts decaprenylphosphoryl‐beta‐ d ‐ribose (DPR) to decaprenylphosphoryl‐beta‐ d ‐arabinofuranose (DPA), an essential cell wall component 1. Conditional knockdown studies showed that loss of dprE1 results in a strong bactericidal effect in vitro 2.…”
mentioning
confidence: 99%
“…However, the phospholipid phosphatase involved has not been identified yet. The presence of an unknown PAP2-family phospholipid phosphatase (Rv3807c) located next to the phosphoribosyltransferase (Rv3806c) was predicted to catalyze the reaction of dephosphorylation [11]. In this study, we constructed the recombinant plasmid pColdII-Rv3807c to clone and express the Rv3807c gene and identified the localization, functional and structural characteristics of the Rv3807c protein to enable further confirmatory study on the relationship between Rv3807c and DPA biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Ethambutol, a first-line drug for treatment of TB with pleiotropic effects, however, does not block the synthesis of DPA [11], which directly influence AG biosynthesis, even the formation of the cell wall in mycobacterium [10,17]. It remains to be determined whether the speculated enzyme Rv3807c catalyses the conversion of DPPR to DPR and its precise role in the biosynthesis of DPA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations